2021
DOI: 10.1186/s12958-021-00758-5
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-30a-5p promotes differentiation in neonatal mouse spermatogonial stem cells (SSCs)

Abstract: Background The importance of spermatogonial stem cells (SSCs) in spermatogenesis is crucial and intrinsic factors and extrinsic signals mediate fate decisions of SSCs. Among endogenous regulators, microRNAs (miRNAs) play critical role in spermatogenesis. However, the mechanisms which individual miRNAs regulate self- renewal and differentiation of SSCs are unknown. The aim of this study was to investigate effects of miRNA-30a-5p inhibitor on fate determinations of SSCs. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 50 publications
1
3
0
Order By: Relevance
“…The high expression for these three markers (PLZF, Thy-1 and α-6 integrin) in SSCs indicated the primary phases of the evolvement of the spermatogenic lineage in isolated SSCs whose differentiation process had not yet initiated and confirmed that SSCs collected after digestion enzymatic were in the undifferentiated stage. The high expression of SSC identification markers in this study was consistent with other studies [ 35 37 ].…”
Section: Discussionsupporting
confidence: 93%
“…The high expression for these three markers (PLZF, Thy-1 and α-6 integrin) in SSCs indicated the primary phases of the evolvement of the spermatogenic lineage in isolated SSCs whose differentiation process had not yet initiated and confirmed that SSCs collected after digestion enzymatic were in the undifferentiated stage. The high expression of SSC identification markers in this study was consistent with other studies [ 35 37 ].…”
Section: Discussionsupporting
confidence: 93%
“…Similarly, in olive flounder ( Paralichthys olivaceus ), miR-143, miR-26a and let-7a were also identified as the most expressed miRNAs in both ovaries and testes (Gu et al, 2014). In mouse and human, miR-30a-5p was crucial for spermatogonial stem cell differentiation (Khanehzad et al, 2021) and was used as a marker for men suffering from non-obstructive azoospermia (Arefnia et al, 2022). In our data, however, we observed a conserved overexpression of miR-30a in adult fish ovaries compared to adult testes in the ten studied species.…”
Section: Discussionmentioning
confidence: 99%
“…Intrinsic factors and extrinsic signals play a crucial role in maintaining a delicate balance between SSC proliferation and differentiation, which ensures a continuous supply of differentiating spermatogonia while preserving an adequate population of stem cells ( 75 ) and ensuring the lifelong production of spermatozoa. miRNAs are important endogenous regulators of this process in spermatogenesis ( 76 ).…”
Section: Mechanism Of Mirna Involved In Spermatogenesismentioning
confidence: 99%
“…The inhibition of SSC differentiation by downregulating Plzf expression and upregulating Stra8, Dazl, and Sycp3 expression ( 80 ). Inhibition of miR-30a-5p triggers the differentiation of neonatal mouse SSCs ( 76 ), whereas its overexpression increases cell viability and promotes antiapoptotic and antioxidant activities during the freeze-thaw process of SSCs ( 81 ). SC-derived exosomal miR-30a-5p promotes the proliferation and differentiation of SSCs by regulating the MAPK signaling pathway through Zeb2/Fgf9 ( 82 ).…”
Section: Mechanism Of Mirna Involved In Spermatogenesismentioning
confidence: 99%